Prospective registry of symptomatic severe aortic stenosis in octogenarians: a need for intervention. (27th March 2014) - Martínez‐Sellés, M.; Gómez Doblas, J. J.; Carro Hevia, A.; García de la Villa, B.; Ferreira‐González, I.; Alonso Tello, A.; Andión Ogando, R.; Ripoll Vera, T.; Arribas Jiménez, A.; Carrillo, P.; Rodríguez Pascual, C.; Casares i Romeva, M.; et al.
Abstract Objective To study the factors associated with choice of therapy and prognosis in octogenarians with severe symptomatic aortic stenosis (AS). Study Design Prospective, observational, multicenter registry. Centralized follow‐up included survival status and, if possible, mode of death and Katz index. Setting Transnational registry in Spain. Subjects We included 928 patients aged ≥80 years with severe symptomatic AS. Interventions Aortic‐valve replacement (AVR), transcatheter aortic‐valve implantation (TAVI) or conservative therapy. Main outcome measures All‐cause death. Results Mean age was 84.2 ± 3.5 years, and only 49.0% were independent (Katz index A). The most frequent planned management was conservative therapy in 423 (46%) patients, followed by TAVI in 261 (28%) and AVR in 244 (26%). The main reason against recommending AVR in 684 patients was high surgical risk [322 (47.1%)], other medical motives [193 (28.2%)], patient refusal [134 (19.6%)] and family refusal in the case of incompetent patients [35 (5.1%)]. The mean time from treatment decision to AVR was 4.8 ± 4.6 months and to TAVI 2.1 ± 3.2 months, P < 0.001. During follow‐up (11.2–38.9 months), 357 patients (38.5%) died. Survival rates at 6, 12, 18 and 24 months were 81.8%, 72.6%, 64.1% and 57.3%, respectively. Planned intervention, adjusted for multiple propensity score, was associated with lower mortality when compared with planned conservative treatment: TAVI Hazard ratio (HR) 0.68 (95% confidence interval [CI] 0.49–0.93; P = 0.016) and AVR HR 0.56 (95% CI 0.39–0.8; P = 0.002). Conclusion Octogenarians with symptomatic severe AS are frequently managed conservatively. Planned conservative management is associated with a poor prognosis.